Le shopping mall : un modèle pour la construction de la ville ? - Anaïs Daniau (Ateliers d'Anthropologie)
After having shown the extent to which the revival of the “shopping mall” concept was inspired by the city, this article aims to symmetrize the analysis of this relationship by describing how the management of urban centers is borrowing from the operation of shopping malls in order to reinvent these centers. In my view, city center managers’ increasing reference to the shopping mall as a model of efficiency reveals the existence of broader processes affecting our city centers and the way these are managed: the homogenization of central spaces, the rise of a managerial and entrepreneurial vision of territory, the development and professionalization of city commodification practices.